Ökonomische Wurzeln des Populismus - Thieß Petersen (Wirtschaftsdienst, 2018)
Das politische Modell einer liberalen und weltoffenen Demokratie gerät in vielen westlichen Industrieländern zunehmend unter Druck. Stattdessen nehmen populistische Tendenzen zu. Dieser Betrag skizziert die ökonomischen Ursachen für das Erstarken populistischer Parteien und Politiker in entwickelten westlichen Volkswirtschaften. – – Increasing populism in developed Western countries such as Germany can be traced to various causes, including economic ones. In these countries, advancing globalisation and technological progress lead to labour market and income effects that have had a negative impact on certain groups of people (wage reduction, increase in the risk of unemployment). The fear of such developments - whether justified or unfounded - results in the desire for political decisions that push back the catalysts of these economic developments. Therefore, international trade with low-wage countries and labour saving technological progress in particular often breed populist parties.
Keywords: A13; E25; F16; 330